2016
DOI: 10.1016/j.immuni.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Stromal Cells Control Local CD8 + T Cell Responses during Virus-Induced Neuroinflammation

Abstract: Stromal cells generate a complex cellular scaffold that provides specialized microenvironments for lymphocyte activation in secondary lymphoid organs. Here, we assessed whether local activation of stromal cells in the central nervous system (CNS) is mandatory to transfer immune recognition from secondary lymphoid organs into the infected tissue. We report that neurotropic virus infection in mice triggered the establishment of such stromal cell niches in the CNS. CNS stromal cell activation was dominated by a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 49 publications
7
89
1
1
Order By: Relevance
“…Elevated CCL21 mRNA was also noted in CXCL13 Ϫ/Ϫ and CXCR3 Ϫ/Ϫ mice (11,24). Following infection with the JHMV heterologous MHV-A59 strain, CCR7 ligands produced by CNS stromal cells were crucial to support recruitment and local reactivation of antiviral CD8 ϩ T cells (86). These studies indicated that CNS stromal cells generate confined microenvironments that control T cell immunity and protect the host from lethal neuroinflammatory disease.…”
Section: Discussionmentioning
confidence: 86%
“…Elevated CCL21 mRNA was also noted in CXCL13 Ϫ/Ϫ and CXCR3 Ϫ/Ϫ mice (11,24). Following infection with the JHMV heterologous MHV-A59 strain, CCR7 ligands produced by CNS stromal cells were crucial to support recruitment and local reactivation of antiviral CD8 ϩ T cells (86). These studies indicated that CNS stromal cells generate confined microenvironments that control T cell immunity and protect the host from lethal neuroinflammatory disease.…”
Section: Discussionmentioning
confidence: 86%
“…More recently, a marked increase in the frequency of PDGFRα + PDGFRβ + Cadherin-11 + ICAM-1 + fibroblasts has also been identified within cerebral lesions of mice that develop experimental autoimmune encephalomyelitis (EAE) (64). Recently, endothelial cells and perivascular fibroblasts of the brain were shown to nucleate local CD8 + T cell responses to a neurotropic virus by expressing CCR7 ligands (65). As TLS-associated LTo-like cells are considered resident and long-lived, in comparison to the circulating and short-lived hematopoietic cells, they may hold the key to the reversibility of TLS assembly, providing an interesting therapeutic target for this process.…”
Section: Lymphoid Stromal Cell Differentiation In Slos and Tlsmentioning
confidence: 99%
“…First, the expression of MHC molecules is limited within the CNS parenchyma. Second, the entry of adaptive immune cells into the CNS via the blood-cerebrospinal fluid (CSF) barrier, the CSF-brain barrier, and the blood-brain barrier is restricted, but immune surveillance of the CNS does take place (33,34). The clinical presentation of ZIKV-infected Ifnar1 Ϫ/Ϫ mice, along with the previously described tropism of ZIKV for neurons, suggest that CD8 ϩ T cells may migrate to CNS when virus infects the neuron cells.…”
Section: Cd8 ϩ T Cell Immune Response In Zika Virus Infectionmentioning
confidence: 99%